The Effect of Corporate Social Responsibility, Intellectual Capital, and Firm Size on Company Financial Performance (Empirical Study of Manufacturing Companies Listed on the Indonesia Stock Exchange in 2019–2021) - Lovinza; Wiralestari; Rahayu (International Journal of Integrative Sciences, 2023)
The purpose of this research is to examine the impact of corporate social responsibility, intellectual capital, and firm size on corporate financial performance. Which is measured by return on Assets (ROA). This research is a form of quantitative research. Secondary data gathered from www.idx.co.id and the company's website is used. This study's population consists of manufacturing businesses registered on the Indonesia Stock Exchange in 2019-2021. While the sample of this study was determined using purposive sampling, so that a total of 183 data points could be processed. The analysis method used is multiple linear regression analysis using SPSS version 25. According to the findings of this study, corporate social responsibility has no influence on the financial performance of a business. This indicates that the high and low disclosure of corporate social responsibility has no influence on the corporate financial performance. While intellectual capital and firm size have an impact on the corporate financial performance